Vascular Endothelial Growth Factor-B Induces a Distinct Electrophysiological Phenotype in Mouse Heart - Naumenko, Nikolay; Huusko, Jenni; Tuomainen, Tomi; Koivumäki, Jussi T.; Merentie, Mari; Gurzeler, Erika; Alitalo, Kari; Kivelä, Riikka; Ylä-Herttuala, Seppo; Tavi, Pasi (Frontiers in Physiology, 2017)
Vascular endothelial growth factor B (VEGF-B) is a potent mediator of vascular, metabolic, growth and stress responses in the heart, but the effects on cardiac muscle and cardiomyocyte function are not known. The purpose of this study was to assess the effects of VEGF-B on the energy metabolism, contractile and electrophysiological properties of mouse cardiac muscle and cardiac muscle cells. In vivo and ex vivo analysis of cardiac-specific VEGF-B TG mice indicated that the contractile function of the TG hearts was normal. Neither the oxidative metabolism of isolated TG cardiomyocytes nor their energy substrate preference showed any difference to WT cardiomyocytes. Similarly, myocyte Ca2+ signalling showed only minor changes compared to WT myocytes. However, VEGF-B overexpression induced a distinct electrophysiological phenotype characterised by ECG changes such as an increase in QRSp time and decreases in S and R amplitudes. At the level of isolated TG cardiomyocytes, these changes were accompanied with decreased action potential upstroke velocity and increased duration (APD60-70). These changes were partly caused by downregulation of sodium current (INa) due to reduced expression of Nav1.5. Furthermore, TG myocytes had alterations in voltage-gated K+ currents, namely decreased density of transient outward current (Ito) and total K+ current (Ipeak). At the level of transcription, these were accompanied by downregulation of Kv channel-interacting protein 2 (Kcnip2), a known modulatory subunit for Kv4.2/3 channel. Cardiac VEGF-B overexpression induces a distinct electrophysiological phenotype including remodelling of cardiomyocyte ion currents, which in turn induce changes in action potential waveform and ECG.